Air-stable, storable, and highly efficient chiral zirconium catalysts for enantioselective Mannich-type, aza Diels–Alder, aldol, and hetero Diels–Alder reactions - Kobayashi, Shū (National Academy of Sciences, 2004)
For the synthesis of optically active compounds, chiral catalysts have attracted much attention because large quantities of optically active molecules can be prepared from a small amount of a chiral source. However, many chiral catalysts are often unstable in air (oxygen) and/or in the presence of water. This is especially the case in chiral Lewis acid catalysis, because most Lewis acids are air- and moisture-sensitive. Therefore, many catalysts are prepared in situ in an appropriate solvent just before use, and they cannot be stored for extended periods. We have developed air-stable, storable, and highly efficient chiral zirconium Lewis acids. The catalysts promoted asymmetric Mannich-type, aza Diels–Alder, aldol, and hetero Diels–Alder reactions efficiently with high enantioselectivities. A key to stabilizing the catalysts is an appropriate combination of chiral zirconium Lewis acids with molecular sieves, and the zirconium–molecular sieves-combined catalysts can be stored for extended periods in air at room temperature without loss of activity. Moreover, it has been demonstrated that the catalysts can be recovered and reused.